Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

Two unusual stereoisomeric dammarane-type triterpenoid saponins from the leaves of Panax japonicus (T. Nees) C. A. Mey - Yezi Ma; Linwei Dan; Wei Wang; Yuze Li; Xiaomei Song; Hao Fan; Dongdong Zhang (Natural Product Research, 2026)

Experimental investigation of bubble morphology and instantaneous impact characteristics in submerged jets - Yongfei Yang; Wenxiao Wang; Weidong Shi; Xianglong Wu; Linwei Tan; Yupeng Cao; Yu Lu; Chunhui Ma (Ocean Engineering, 2026)

lncRNA DLGAP1-AS2 Modulates the TGF-β/Smad Signaling Pathway to Regulate Epithelial-Mesenchymal Transition in Renal Cell Carcinoma - Honghao Cao; Junlong Zhu; Ling Zhang; Linwei Li; Langchuan Ma; Chenchen Xie (Biochemical Genetics, 2026)

Hydrogen integration in China’s aviation sector: Techno-economic optimization for flight network decarbonization - Maximilian Arras; Falk Zimmer; Alexander Rau; Wubin Yan; Zheng Li; Linwei Ma (Resources, Conservation and Recycling, 2026)

Optimization of the initial performance of solid oxide fuel cells base on reduction and operating temperature - Peiyuan Liu; Xiaoyu Wang; Linwei Ma; Minfang Han (Chemical Engineering Journal, 2026)

The unwetted height of transom-stern monohull ships and the Neumann–Michell ship flow computations - Chao Ma; Haolin Yang; Linwei Wang; Yingjiang Zhao; Jie Gong; Zhenlong Fang (Ocean Engineering, 2025)

From Kelvin Wave Patterns to Ship Displacement: An Inverse Prediction Framework Based on a Hull Form Database - Chao Ma; Linwei Wang; Yingjiang Zhao; Haolin Yang; Haoqing Huang; Bohan Cao (Journal of Marine Science and Engineering, 2025)
The estimation of a ship’s displacement volume, ∇, from remote sensing data is of considerable practical value for maritime surveillance and vessel characterization. This paper introduces a practical framework for the inverse estimation of displacement volume from Kelvin ship waves, building upon a prior study through two key extensions. First, the wave amplitude function is recovered using Fourier series expansions combined with the stationary phase method. The displacement volume is then estimated via a two-step procedure: an initial estimate is obtained by identifying a hull with similar amplitude characteristics from a database, followed by a refinement that incorporates discrepancies between the target and candidate wave amplitude functions. In the case studied, the proposed approach achieves a prediction error of 4.02%, demonstrating its potential for non-invasive extraction of hull information from remote sensing data.

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Genetic assessment of feed efficiency in the spotted Babylon Babylonia areolata - Linwei Nie; Yijie Kong; Ziyi Ma; Jingqiang Fu; Shengtai Liu; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2025)

A preliminary assessment of CO2 capture, transport, and storage network for China's steel sector - Yuancheng Lin; Tubagus Aryandi Gunawan; Cecelia Isaac; Hongxi Luo; Fangwei Cheng; Eric D. Larson; Chris Greig; Linwei Ma; Zheng Li (Journal of Cleaner Production, 2024)

Methane emission and influencing factors of China's oil and natural gas sector in 2020–2060: A source level analysis - Shuo Sun; Linwei Ma; Zheng Li (Science of The Total Environment, 2023)

Coordinating energy and material efficiency strategies for decarbonizing China's iron and steel sector - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Understanding the drivers of CO2 growth in China's iron and steel sector: An integrated analysis of the energy–material–economy nexus - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

How will China's steel demand develop under the investment-driven patterns? Integrating extended input-output model with dynamic steel flow analysis - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

A supply chain allocation method for environmental responsibility based on fossil energy as the anchor for carbon responsibility - Chin Hao Chong; Yuan Gao; Linwei Ma; Zheng Li; Weidou Ni; Xiaoyong Zhou; Silvio Cristiano; Fanxin Meng; Wen Zhang; Ningyu Yan; Yan Hao; Gengyuan Liu (Journal of Cleaner Production, 2023)

Slope Instability Analysis of the Qiongdongnan Basin in the Northern Part of the South China Sea: Implications for the Risk Evaluation of Deepwater Drilling - Linwei Ma; Shiguo Wu; Yanrui Liu; Jin Sun; Min Ouyang; Qingping Li; Yongpeng Qin; Dawei Wang (Journal of Ocean University of China, 2023)